Understanding the need for planning for public administrators: An examination of planning courses and concentrations in NASPAA member programs. (2nd January 2021) - Meares, Wesley
ABSTRACT: Public administration scholarship of teaching and learning has given little attention to planning curriculum, despite that planning is becoming more relevant to public administrators. This notion of increasing importance can be perceived at all levels of government, but it is most visible at the local level. The purpose of this research is to examine course offerings of the member programs of the Network of Schools of Public Policy, Affairs, and Administration (NASPAA) to understand the degree that planning courses and concentrations are integrated with public administration education. Additionally, I examined the accreditation standards of NASPAA and the Association of Collegiate Schools of Planning (ACSP) in order to further explore the relationship between public administration and planning. The introduction of planning courses can prepare public administrators for planning issues and help develop their ability to communicate, mitigate, and offer potential solutions to these issues.